Preconditioned Conjugate Gradient and Multigrid Methods for Numerical Solution of Multicomponent Mass Transfer Equations II. Convection-Diffusion-Reaction Equations - Juncu, Gheorghe; Nicola, Aurelian; Popa, Constantin; Stroila, Elena (Numerical heat transfer. Part A, Applications, 2014)
This work continues our previous analysis concerning the performances of the nonlinear multigrid (the Full Approximation Storage algorithm) method and modified Picard preconditioned conjugate gradient methods for the numerical solution of the two-dimensional, steady-state, multicomponent mass transfer equations. The present test problems are steady-state, linear and nonlinear, convection-diffusion-reaction equations. The upwind finite difference method was used to discretize the mathematical model equations. The numerical results obtained show good numerical performances.